Evaluation of Cocoa Bean Shell Antimicrobial Activity: A Tentative Assay Using a Metabolomic Approach for Active Compound Identification - Rojo-Poveda, Olga; Ribeiro, Sofia Oliveira; Anton-Sales, Cèlia; Keymeulen, Flore; Barbosa-Pereira, Letricia; Delporte, Cédric; Zeppa, Giuseppe; Stévigny, Caroline (Planta Medica, 2021)
Cocoa bean shell is one of the main by-products of chocolate manufacturing and possesses several compounds with biofunctionalities. It can function as an antibacterial agent, and its action is mostly reported against Streptococcus mutans. However, only a few studies have investigated the cocoa bean shell compounds responsible for this activity. This study aimed to evaluate several extracts of cocoa bean shells from different geographical origins and cocoa varieties and estimate their antimicrobial properties against different fungal and bacterial strains by determining their minimal inhibitory concentration. The results demonstrated antimicrobial activity of cocoa bean shell against one of the tested strains, S. mutans. Cocoa bean shell extracts were further analysed via LC-HRMS for untargeted metabolomic analysis. LC-HRMS data were analysed (preprocessing and statistical analyses) using the Workflow4Metabolomics platform. The latter enabled us to identify possible compounds responsible for the detected antimicrobial activity by comparing the more and less active extracts. Active extracts were not the most abundant in polyphenols but contained higher concentrations of two metabolites. After tentative annotation of these metabolites, one of them was identified and confirmed to be 7-methylxanthine. When tested alone, 7-methylxanthine did not display antibacterial activity. However, a possible cocktail effect due to the synergistic activity of this molecule along with other compounds in the cocoa bean shell extracts cannot be neglected. In conclusion, cocoa bean shell could be a functional ingredient with benefits for human health as it exhibited antibacterial activity against S. mutans. However, the antimicrobial mechanisms still need to be confirmed.
Keywords: cocoa bean shell; Theobroma cacao; Malvaceae; antimicrobial activity; Streptococcus mutans; metabolomics